The Influence of Intelligence Quotient (Iq) Towards The Speed Reading Ability - Nurwahidah, Lina Siti; Kartini, Ari; Anggela, Inggit (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study deals with the influence of intelligence quotient (IQ) towards the speed-reading ability among high school students in Garut. It aims to reveal whether an individual’s IQ influences his ability to read quickly. This quantitative study used correlational description methods. To gather the data, a test and documentation study were applied involving 40 high school students that were selected through probability sampling technique. The results of the study revealed: 1) Spearman correlation test was conducted due to non-normal data distribution, 2) the Spearman correlation test, Sig 0,754 > alfa 0,05, means IQ level had no significant influence towards students’ speed reading ability, 3) Other factors contributing to the result might be related to: students’ interest and motivation in reading as well as students’ reading habit or activities that may distract them such as vocalisation, lips movements, head movements, regression, and sub-vocalisation.